UPAYA GURU BIMBINGAN DAN KONSELING DALAM MEMBANGKITKAN MOTIVASI BELAJAR SISWA DI SMP NEGERI 2 PANGKALAN KURAS KECAMATAN PANGKALAN KURAS KABUPATEN PELALAWAN - Awaluddin (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
The background of this study lies in the low level of students’ learning motivation. This study aims to improve students’ motivation through the efforts of guidance teachers. The research employed a classroom action research design. Based on the results of questionnaire data processing, the guidance teachers’ efforts in motivating students’ learning were generally categorized as good. Data were collected using a questionnaire administered to 30 students consisting of 12 items. The results indicate that the dominant response was SS (very often). Therefore, it can be concluded that the efforts of guidance teachers to enhance students’ learning motivation at SMPN 2 Pangkalan Kuras, Pangkalan Kuras District, are classified as fairly good.